Regional Head’s Authority In Determining Mutation Of Government Employees - Fahmi Kamuli; Tunggul Anshari; Istislam Istislam (Jambura Law Review, 2021)
This research is aimed to analyzing and understanding the actions of the Head of Boalemo Regency in mutate the Civil Servant based on the mutation policy and also to analyze the filling positions in the implementation of the mutation of Civil Servants in Boalemo Regency. The method used in this research is Empirical Juridical Method. The results of the research were found that mutations of Civil Servant are enhancement over the years in Boalemo Regency. Injustice in determining mutations is marked by work placements that are not compatible with Civil Servants’ educational background. There is a political interest in the Government of Boalemo Regency which caused injustice in the mutation of the Civil Servants.